2022
DOI: 10.3389/fmicb.2022.1019010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salinity on the diversity and composition of carbohydrate metabolism, nitrogen and sulfur cycling genes in lake surface sediments

Abstract: Exploring functional gene composition is essential for understanding the biogeochemical functions of lakes. However, little is known about the diversity and composition of biogeochemical cycling genes and their influencing factors in saline lakes. In this study, metagenomic analysis was employed to characterize the diversity and composition of microbial functions predicted from genes involved in carbohydrate metabolisms, nitrogen, and sulfur cycles in 17 surface sediments of Qinghai-Tibetan lakes with salinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Sulfur cycle genes could be regulated by salinity. The abundances of some genes related to dissimilatory sulfur reduction and oxidation, the link between inorganic and organic sulfur transformation, and sulfur disproportionation and reduction decreased with increasing salinity, while genes involved in assimilatory sulfate reduction and sulfur oxidation tended to increase ( Liu, Q. et al, 2022 ). In the present study, some genes related to the sulfur cycle increased in 101-14 after treatment with NaCl.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfur cycle genes could be regulated by salinity. The abundances of some genes related to dissimilatory sulfur reduction and oxidation, the link between inorganic and organic sulfur transformation, and sulfur disproportionation and reduction decreased with increasing salinity, while genes involved in assimilatory sulfate reduction and sulfur oxidation tended to increase ( Liu, Q. et al, 2022 ). In the present study, some genes related to the sulfur cycle increased in 101-14 after treatment with NaCl.…”
Section: Discussionmentioning
confidence: 99%
“…The decomposition of the composite carbon source generated abundant accessible organic substrates, which furnished the growth of heterotrophic microbes and impacted the composition of microbial community [ 50 ]. Ultimately, the changes in the composition of microbial communities led to variations in the composition of functional genes closely related to taxonomic composition [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The decomposition of the composite carbon source generated abundant accessible organic substrates, which furnished the growth of heterotrophic microbes and impacted the composition of microbial community [50]. Ultimately, the changes in the composition of microbial communities led to variations in the composition of functional genes closely related to taxonomic composition [51]. In terms of the denitrification functional genes, the prevailing functional genes of denitrification in C0 and C5 were napA and napB, which can encode nitrate reductase and promote the conversion of nitrate to nitrite.…”
Section: Changes In Nitrogen Cycling Processes and Involved Functiona...mentioning
confidence: 99%
“…They found that S changes could reduce ammonium and nitrite oxidation potential to 42%, and other metabolic processes related to the nitrogen cycle were positively influenced. Liu et al (2022) showed that S changes in response to different nutrientcycling genes and found that decreasing S can modify nitrogen metabolic genes in aquatic environments.…”
Section: Prokaryotic Metabolic Potential In Response To the Differenc...mentioning
confidence: 99%